Water Quality Assessment of the Godavari River - Chavan, Ajay D.; Sharma, M P; Bhargava, Renu (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The Godavari River is a second largest river in India originating from Trimbakeswar, Nasik, Maharashtra, India. It fl ows through the states of Madhya Pradesh, Karnataka, Orissa and Andhra Pradesh. The river, passing through Nasik City, is 82% polluted by domestic pollution and 18% by industries. The study covers about 65 km of the river starting from Kushawart Trimbakeswar to Saikheda Village, from where it enters the city. Ten locations were selected for collection of water samples from the river and the samples were analyzed for water quality parameters in the Environmental Laboratory of the Maharashtra Pollution Control Board (MPCB), Nasik. These data as well as data from the Central Pollution Control Board (CPCB) were used to compute the National Sanitation Foundation Water Quality Index (NSFWQI), mostly applicable in the USA and India. The results of NSFWQI of Godavari River indicates its water quality as ‘bad’ (26-50) or ‘medium’ (51-70) over the study stretch. The NSFWQI of December 2007 and February 2008 indicate an improvement in water quality at all locations over earlier data from 2002-07. Based upon the results, the existing conservation measures have been reviewed and additional measures are suggested. The study concludes that major stressor is sewage pollution. Key words: Water quality parameters; Water quality assessment; Water quality management; Conservation measures DOI: 10.3126/hn.v5i0.2483 Hydro Nepal Vol. 5, July 2009 Page:31-34